HUBUNGAN PENGETAHUAN DAN PERILAKU KELUARGA DENGAN RESIKO JATUH PADA LANSIA DI UPT PUSKESMAS KEDAI DURIAN KEL. DURIAN, KEC. MEDAN JOHOR - EKA ISRANIL LAILY (LP2MTBM MAKARIOZ, 2021)
Falls are one of the leading causes of death and injury in the elderly population. Twenty to thirty percent of the elderly have a high degree of disability related to falls. To prevent the elderly from falling at risk, it is necessary to have good knowledge and behavior carried out by the closest people to the elderly, for example children, grandchildren, in-laws or other family members. Through good knowledge and behavior, a safe environment will be created for the elderly. Based on a preliminary study conducted by researchers on February 8, 2021 in the working area of ​​the UPT Puskesmas Kedai Durian Kel. Durian District. Medan Johor found the number of elderly as many as 200 elderly. Researchers conducted interviews with elderly families who accompanied the elderly at the health center. 7 elderly people had fallen at home, 6 elderly people after falling recovered and carried out their usual activities and 1 elderly person after falling had a hip fracture and had difficulty moving. knowledge and behavior of families with the risk of falling in the elderly at UPT Puskesmas Kedai Durian Kel. Durian District. Medan Johor. The sample in this study was an elderly family of 40 people, sampling was Accidental Sampling. The results showed that the respondents' knowledge of the risk of falls in the elderly was mostly good knowledge of 30 people (75%), the majority of respondents' behavior was good as many as 32 people (80%). The results of the chi square test showed a significant relationship between the respondent's knowledge and the risk of falling in the elderly with p = 0.001, and the uchi square test results showed a significant relationship between the respondent's behavior and the risk of falling in the elderly with p = 0.007. It is hoped that the Puskesmas will add health promotion programs about preventing falls in the elderly by distributing brochures and providing counseling in every village.